Fatigue Analysis Aluminium 6063-TF on the Rotary Bending Testing Machine - Ery Diniardi; Boy Setiawan; Anwar Ilmar Ramadhan (Journal of Applied Sciences and Advanced Technology, 2019)
Some of the damage that occurs in the structure and construction of engine elements that experience dynamic loading at the time of operation is caused by fatigue (fatigue), which occurs without beginning signs so that it causes great damage and loss. Fatigue strength is the process of local changes in the structure that occur permanently in accordance with the period of time caused by conditions where stress or strain occurs which results in cracks or fractures after being subjected to repetitive loads. Surface roughness factors that affect fatigue are applied in the analysis and application of machining, which are finely grinded and rough machined. Analysis was carried out on 6063-TF aluminum alloy material which is widely used for motor vehicles. To find out the effect of the above, the fatigue strength test is carried out with a Rotary Bending Fatique Test to obtain a cycle value or fatigue age and certain neighbors so that it can make a semi-log S-N diagram with statistical calculations.